Sensory preference and mineral contents of cereal bars made from glutinous rice flakes and Sunnah foods - Rafiu Agbaje; Chek Zaini Hassan; Norlelawati Arifin; Asma Abdul Rahman (International Organization of Scientific Research, 2024)
Non-Indexed Publication